Pengaruh Prinsip Character, Capacity, Capital, Collateral, Condition Of Economy Terhadap Pengambilan Keputusan Kredit PT. Bank Negara Indonesia KCU Cibinong Tahun 2020 - Ependi Ependi; Muhammad Awwabin (Universitas Mohammad Husni Thamrin, 2020)
Bank Is A Financial Intermediary Institution Generally Established With The Authority To Manage Money Deposits. In Giving Credit There Are Several Things That Are Associated With Good Faith (Willingness To Pay) And Ability To Pay (Ability To Pay). Having the Problem Formulation Above Analyzing the Influence of These Factors is Very Important, namely